Erica Tietze-Conrat, Tagebücher (1923-1926) Band I: Der Wiener Vasari - Caruso, Alexandra (2015)
In her early diaries the art historian Erica Tietze-Conrat discribes her eventfull life in Vienna in the 1920ies, were she had been in touch with all the important art circles of the time..